Long-Term Use of Metronidazole Mimicking Hepatic Encephalopathy - Umar Ghaffar; Kiran Lukose; Mohammad As Sayaideh; Bhagwan Dass; Nila S. Radhakrishnan (Annals of Internal Medicine: Clinical Cases)
Metronidazole, a widely used antibiotic is associated with a rare but serious set of adverse effects termed Metronidazole Induced Encephalopathy. This condition can be related to both short as well as long term use of the drug and manifests itself as a constellation of symptoms of neurotoxicity, which can include cerebellar dysfunction, speech abnormalities, seizures and an altered sensorium. In addition to a history and physical exam the backbone of diagnosis for this condition is a set of specific findings seen on Magnetic resonance imaging of the brain.